2004
DOI: 10.1007/s00414-004-0448-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug analysis in blowfly larvae and in human tissues: a comparative study

Abstract: The present study investigates the correlation between concentrations of drugs in human tissues and Diptera larvae feeding on these tissues. Samples of liver were taken from 18 cases in which preliminary toxicological screening indicated the presence of drugs. Blowfly larvae (Diptera: Calliphoridae) were reared on these samples and subsequently analyzed for drug content. Toxicological analyses were carried out using ONLINE Abuscreen (Roche) and GC/MS for available body fluids (blood, urine and bile) as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 30 publications
7
50
0
7
Order By: Relevance
“…For each definite compound, i) the concentrations in larvae were generally much lower than those in the cadaveric samples, ii) no correlation was observed between the concentrations measured in the larval compared to the human material. These results completely agree with those of another recent study [23]. As an example, in 4 fatalities of our series involving nordiazepam (always combined with other xenobiotics), blood-to-larvae ratios for this drug were in the range 1:23, and liver-to-larvae ratios in the range 3:38.…”
Section: Resultssupporting
confidence: 94%
“…For each definite compound, i) the concentrations in larvae were generally much lower than those in the cadaveric samples, ii) no correlation was observed between the concentrations measured in the larval compared to the human material. These results completely agree with those of another recent study [23]. As an example, in 4 fatalities of our series involving nordiazepam (always combined with other xenobiotics), blood-to-larvae ratios for this drug were in the range 1:23, and liver-to-larvae ratios in the range 3:38.…”
Section: Resultssupporting
confidence: 94%
“…While the screening results were beyond doubt, quantitation was less clear. However, our findings correspond to those demonstrated in other studies where organic compounds, including amphetamine, were identified (4,5,7). These studies found no correlation between drug concentrations in human material and larvae found on human corpses.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that the accumulation of drugs in larvae is unpredictable and quantitation unreliable. Although there are researchers who are still sceptical about the usefulness of entomotoxicology in forensic medicine, we believe that all reasonable steps should be taken to perform a comprehensive toxicological analysis, if such is required to clear doubts related to a case (4,5). We always have to keep in mind factors affecting toxicological analyses and the limitations of their interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it seems very likely that the lyophilized tissue ingested by the maggots contains relevant drug levels of immunosuppressants. Unfortunately, it is not possible to compare tissue levels and drug concentrations within the larvae because of differences in eliminating drugs with varying efficiency [13, 14]. Therefore, immunosuppression with cyclosporine A in patient 1 and with azathioprine in patient 2 (though being stopped 1 week before) may have contributed to the decreased survival time of larvae.…”
Section: Discussionmentioning
confidence: 99%